Caracterização de uma nova linhagem de célula dendrítica: AP284 - Oliveira, Pollyana Guimarães de (2014)
Dendritic cells (DCs) are a heterogeneous group of cells and the major activators of naive T lymphocytes. During antigen presentation, different types of cytokines are produced and they will interfere with the immune response profile generated. IL-12p70 promotes the differentiation of Th1 phenotype and IL-23 p enhances the Th17 response. Given the major role of IL-12 and IL-23 on the stabilization of the acquired immune response, the production of these cytokines is highly controlled and it is an issue for several studies. The objective of this work was to characterize a new lineage of DC, described as AP284, based on their surface markers and evaluate the ability of these cells to produce IL-12p40, IL-12p70 and IL-23 after different stimulus in vitro. Additionally it will be evaluate their phagocytic capacity and their ability to induce a Th1 and Th17 response in vivo. The expression of the markers was analyzed by flow cytometry and the quantitation of IL-12 and IL23 was performed by ELISA after stimulation of cells AP284 in vitro with lipopolysaccharide (LPS) and Escherichia coli. AP284 cells express MHC class II, CD11c and 33D1 on its surface, which are characteristic markers of DCs. After stimulus with LPS or E.coli, AP284 cells produce large amounts of IL-12p40 and IL-23 but do not produce IL-12p70. The production of IL-12p70 was not detected even when IFN-γ is added to prime cultures, moreover, priming the cells with IFN-γ promoted inhibition of IL-12p40 and IL-23. Our data sugest that the AP284 is a DC17 lineage. Thus, AP284 can be an important tool to study the mechanisms of induction or regulation of IL-23 production and a possible tool to study generation and maintenance of a Th17 profile.